2021
DOI: 10.1021/acscatal.1c04799
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Hydroboration of Esters by Versatile Thorium and Uranium Amide Complexes

Abstract: The challenging hydroboration of esters is achieved using simple uranium and thorium amides, U­[N­(SiMe3)2]3 and [(Me3Si)2N]2An­[κ2-(N,C)-CH2Si­(CH3)2N­(SiMe3)] (An = Th or U) acting as precatalysts in the reaction with pinacolborane (HBpin). All three complexes showed impressive catalytic activities, reaching excellent yields. A large scope of esters was investigated including aliphatic, aromatic, and heterocyclic esters that were transformed cleanly to the corresponding hydroborated alcohols, which readily h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 84 publications
(109 reference statements)
1
26
0
Order By: Relevance
“…Examples of catalytic reactions mediated by uranium complexes have appeared in recent decades. [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83] For example, Meyer and coworkers reported an example of uranium-mediated electrocatalytic production of H 2 from H 2 O. 76,77 Recently, Arnold and coworkers demonstrated that a dinuclear uranium complex could bind N 2 , mediating its reduction and functionalization to NH 3 .…”
Section: Articlementioning
confidence: 99%
“…Examples of catalytic reactions mediated by uranium complexes have appeared in recent decades. [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83] For example, Meyer and coworkers reported an example of uranium-mediated electrocatalytic production of H 2 from H 2 O. 76,77 Recently, Arnold and coworkers demonstrated that a dinuclear uranium complex could bind N 2 , mediating its reduction and functionalization to NH 3 .…”
Section: Articlementioning
confidence: 99%
“…As relatively abundant actinides on earth, thorium and its derivatives have manifested critical applications in nuclear energy, medical, and industrial fields because of their radiation resistance, high temperature resistance, and high thermal conductivity. However, the relatively low structural variability of these materials restricts their development to some extent in more potential applications. The development of thorium-based coordination compounds provides more possibilities to overcome these restrictions, because more structural variations and functional modulations can be readily implemented through the diverse coordination numbers and intriguing coordination modes of thorium as well as coordination of different functional ligands . Particularly, thorium-based metal–organic frameworks (Th-MOFs) have been tuned for applications in gas adsorption, ion exchange, and radiation resistance through coordination modification with different organic ligands. Nevertheless, the application of thorium-based functionalized materials (including thorium-based complexes) in the field of catalysis is still largely unexplored. To date, a mere handful of Th-MOFs have been reported to be applied as heterogeneous catalysts for CO 2 cycloaddition and photocatalytic oxidation of 2-chloroethyl ethyl sulfide. …”
Section: Introductionmentioning
confidence: 99%
“…Findlater found that the efficient hydroboration of esters could be realized using polynuclear lanthanide–diketonato clusters . Recently, Eisen reported an efficient hydroboration of esters promoted by the thorium and uranium amide complexes U­[N­(SiMe 3 ) 2 ] 3 and [(Me 3 Si) 2 N] 2 An­[κ 2 -(N,C)-CH 2 Si­(CH 3 ) 2 N­(SiMe 3 )] (An = Th or U) . Owing to the complex nature of the reported ester hydroboration catalysts, these protocols have much room for improvement, particularly in terms of easily achieved simple catalysts and workup procedure.…”
Section: Introductionmentioning
confidence: 99%